Manhaj ibn AqÄ«l FÄ« al-IstishhÄd bi al-AmthÄl al-Arabiyaah FÄ« Shará¸¥ihin li Alfiah ibn MÄlik - Hong, Han Xiao; Tehhae, Ibrahim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This research aims to study the grammarians position on citing proverbs and other evidence that they relied on in grammatical complexity. The research in this study followed the descriptive analytical approach. This is to describe Ibn Aqil's approach in the issue of citing proverbs and to analyze that scientifically, as well as followed the historical approach in which the research helped in dealing with the events of grammar in history and grammarians and their effects. In the light of the information studied, the research reached the most important results: First: The study proved that Ibn Aqilâ€™s commentary did not celebrate proverbs; Rather, it came in a few; This is due to his reliance - in most cases - on poetry, as is the custom of grammarians. Second: Ibn Aqil mentioned in his explanation of the millennium thirteen examples in grammatical issues, and he mentioned four proverbs in morphological issues. Third: Ibn Aqil followed the approach of the ancient grammarians in citing proverbs alongside other evidence from the Holy Qurâ€™an, or poetry, which is the approach followed by grammarians.ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø¯Ø±Ø§Ø³Ø© Ù…ÙˆÙ‚Ù Ø§Ù„Ù†ØØ§Ø© Ù…Ù† Ø§Ù„Ø§Ø³ØªØ´Ù‡Ø§Ø¯ Ø¨Ø§Ù„Ø£Ù…Ø«Ø§Ù„ ÙˆØ§Ù„Ø£Ø¯Ù„Ø© Ø§Ù„Ø£Ø®Ø±Ù‰ Ø§Ù„ØªÙŠ Ø§Ø¹ØªÙ…Ø¯ÙˆØ§ Ø¹Ù„ÙŠÙ‡Ø§ ÙÙŠ Ø§Ù„ØªÙ‚Ø¹ÙŠØ¯ Ø§Ù„Ù†ØÙˆÙŠØŒ ÙƒÙ…Ø§ ÙŠÙ‡Ø¯Ù Ø¥Ù„Ù‰ Ø§Ù„ÙˆÙ‚ÙˆÙ Ø¹Ù„Ù‰ Ù…Ù†Ù‡Ø¬ Ø§Ø¨Ù† Ø¹Ù‚ÙŠÙ„ ÙÙŠ Ø§Ù„Ø§Ø³ØªØ´Ù‡Ø§Ø¯ Ø¨Ø§Ù„Ø£Ù…Ø«Ø§Ù„ Ù…Ù† Ø®Ù„Ø§Ù„ Ø´Ø±ØÙ‡ Ù„Ù„Ø£Ù„ÙÙŠØ© Ø§Ø¨Ù† Ù…Ø§Ù„Ùƒ. ÙˆØ§ØªØ¨Ø¹ Ø§Ù„Ø¨ØØ« ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠØ› ÙˆØ°Ù„Ùƒ Ù„ÙˆØµÙ Ù…Ù†Ù‡Ø¬ Ø§Ø¨Ù† Ø¹Ù‚ÙŠÙ„ ÙÙŠ Ù‚Ø¶ÙŠØ© Ø§Ù„Ø§Ø³ØªØ´Ù‡Ø§Ø¯ Ø¨Ø§Ù„Ø£Ù…Ø«Ø§Ù„ ÙˆØªØÙ„ÙŠÙ„ Ø°Ù„Ùƒ ØªØÙ„ÙŠÙ„Ø§Ù‹ Ø¹Ù„Ù…ÙŠÙ‘Ø§Ù‹ØŒ ÙƒÙ…Ø§ Ø§ØªØ¨Ø¹ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠ Ø§Ù„Ø°ÙŠ Ø¹Ø§ÙˆÙ† Ø¨Ù‡ Ø§Ù„Ø¨ØØ« ÙÙŠ Ø§Ù„ØªØ¹Ø§Ù…Ù„ Ù…Ø¹ Ø£ØØ¯Ø§Ø« Ø§Ù„Ù†ØÙˆ ÙÙŠ Ø§Ù„ØªØ§Ø±ÙŠØ® ÙˆØ§Ù„Ù†ØØ§Ø© ÙˆØ¢Ø«Ø§Ø±Ù‡Ù…. ÙˆÙÙŠ Ø¶ÙˆØ¡ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ø§Ù„Ù…Ø¯Ø±ÙˆØ³Ø© ØªÙˆØµÙ„ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ù†ØªØ§Ø¦Ø¬ Ø£Ù‡Ù…Ù‡Ø§: Ø£ÙˆÙ„Ø§Ù‹: Ø£Ø«Ø¨ØªØª Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ø´Ø±Ø Ø§Ø¨Ù† Ø¹Ù‚ÙŠÙ„ Ù„Ù… ÙŠØØªÙÙ„ Ø¨Ø§Ù„Ø£Ù…Ø«Ø§Ù„Ø› Ø¨Ù„ Ø¬Ø§Ø¡Øª ÙÙŠÙ‡ Ù‚Ù„ÙŠÙ„Ø©Ø› Ø°Ù„Ùƒ Ù„ØªØ¹ÙˆÙŠÙ„Ù‡ â€“ ÙÙŠ Ø§Ù„Ø£ÙƒØ«Ø±- Ø¹Ù„Ù‰ Ø§Ù„Ø´Ø¹Ø± ÙƒÙ…Ø§ Ù‡ÙŠ Ø¹Ø§Ø¯Ø© Ø§Ù„Ù†ØØ§Ø©. Ø«Ø§Ù†ÙŠØ§Ù‹: Ø£ÙˆØ±Ø¯ Ø§Ø¨Ù† Ø¹Ù‚ÙŠÙ„ ÙÙŠ Ø´Ø±ØÙ‡ Ù„Ù„Ø£Ù„ÙÙŠØ© Ø«Ù„Ø§Ø«Ø© Ø¹Ø´Ø± Ù…Ø«Ù„Ø§Ù‹ ÙÙŠ Ø§Ù„Ù‚Ø¶Ø§ÙŠØ§ Ø§Ù„Ù†ØÙˆÙŠØ©ØŒ ÙƒÙ…Ø§ Ø£ÙˆØ±Ø¯Â Ø£Ø±Ø¨Ø¹Ø© Ø£Ù…Ø«Ø§Ù„ ÙÙŠ Ø§Ù„Ù‚Ø¶Ø§ÙŠØ§ Ø§Ù„ØµØ±ÙÙŠØ©ØŒ Ø«Ø§Ù„Ø«Ø§Ù‹: Ø³Ø§Ø± Ø§Ø¨Ù† Ø¹Ù‚ÙŠÙ„ Ø¹Ù„Ù‰ Ù†Ù‡Ø¬ Ø§Ù„Ù†ØØ§Ø© Ø§Ù„Ù‚Ø¯Ø§Ù…Ù‰ ÙÙŠ Ø§Ù„Ø§Ø³ØªØ´Ù‡Ø§Ø¯ Ø¨Ø§Ù„Ø£Ù…Ø«Ø§Ù„ Ø¨Ø¬Ø§Ù†Ø¨ Ø´ÙˆØ§Ù‡Ø¯ Ø£Ø®Ø±Ù‰ Ù…Ù† Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ…ØŒ Ø£Ùˆ Ø§Ù„Ø´Ø¹Ø± ÙˆÙ‡Ùˆ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù…ØªØ¨Ø¹ Ù„Ø¯Ù‰ Ø§Ù„Ù†ØØ§Ø©.